ETNOSAINS PEMBELAJARAN (PENDEKATAN FILSAFAT SAINS, ONTOLOGI, EPISTEMOLOGI, AKSIOLOGI) DALAM PENDIDIKAN ISLAM - salman, salman (JURNAL ISLAMIKA, 2026)
AbstractThis study aims to analyze the implementation of ethnoscience in the learning process within Islamic Education at MI Al-Falah Bangkinang. The research considers various aspects such as the philosophy of science, ontology, epistemology, and axiology in the context of teaching at the school. The approach used in this study is a qualitative method, which seeks to explore a case study in detail. The findings indicate that incorporating ethnoscience into the Islamic Education curriculum helps students better understand local cultural values and increases their motivation in the learning process. Support for the implementation of ethnoscience includes institutional support from educational organizations, active participation of local communities, and the use of learning media based on cultural values. Keywords: Axiology, Epistemology, Ethnoscience, Philosophy of Science, Health, Education, Islam, and Ontology